Digital Muamalah and Economic Fairness: A Socio-Legal Analysis of FinTech Regulation in Muslim Countries - Asep Koswara (Contemporary Islamic Law and Legal Issue, 2026)
This socio-legal study addresses the central problem of economic fairness in digital mu’āmalah, investigating the tension between technological innovation, Sharia compliance, and consumer protection within FinTech regulation in Muslim countries. Employing a qualitative socio-legal methodology that contrasts doctrinal analysis of regulatory texts (OJK, BNM, DSN-MUI rulings) with assumed empirical data (stakeholder perceptions, public reports on consumer complaints), the research critically assesses the efficacy of current regulatory frameworks. The primary scientific finding reveals a "Compliance-Fairness Paradox," demonstrating that while regulations are successful in ensuring structural compliance (e.g., technical avoidance of ribā and gharar), they fail to guarantee substantive economic fairness (Maqāṣid al-Sharī‘ah). This failure manifests as the Socio-Legal Gap, where legally permissible practices, such as high cumulative fees and algorithmic bias, lead to consumer exploitation and debt traps, fundamentally undermining the Maqāṣid objective of Hifẓ al-Māl (protection of wealth). This study concludes that achieving justice in digital finance requires regulatory policy to shift from a rigid formalistic focus on contractual structure to an adaptive, outcomes-based approach that monitors the social consequences and equitability of FinTech practices.